K strukturi možganov - Rutar, Dušan (Anthropos (Ljubljana), 1989)
The paper deals with the analysis and modelling of brain functions. Three basic characteristics of the system are mentioned: high complexity of the system, the inseparability of the subsystems, and the nature of the empirical data. Besides these characteristics, special attention is paid to three main areas of brain research field: associative memory, parallel processing and self organization.